Penanaman Nilai Religius melalui Program Shalat Dhuha Berjamaah di SMP - Muqorrobin, Syamsul; Iryanto, Rivaldo Kurniawan; Fathoni, Tamrin (Global Education Journal, 2023)
Religious values can help a person to feel more peaceful and happier. This is because religious values can provide hope, optimism, and a strong belief in God or a greater power. This study aims to explain the cultivation of religious values through the Dhuha prayer program in SMP Ma'arif 1 Ponorogo. The research method used is a qualitative approach, a type of phenomenology. Data collection techniques with observation, interviews, and documentation. Data were analyzed by phenomenological analysis with the stages given by Miles and Huberman, namely data condensation, data presentation and conclusions. The results of his research were that the implementation of Duha prayers in congregation at SMP Ma'arif 1 Ponorogo was carried out every Monday-Thursday at 06.45-07.15 all students and teachers always carried out sunnah Duha prayers in an orderly manner. Through the Duha prayer activity program in congregation with efforts to assist teachers in congregational Duha prayers, and the application of discipline and the habit of praying Duha in congregation can foster religious character in SMP Ma'arif 1 Ponorogo students.